“The Way of the Heart” in the Experience and Reflection of St. Augustine - Mejzner, Mirosław (Collectanea Theologica, 2021)
In the writings of St. Augustine, the Latin word cor occurs more than 8,000 times, being one of the most important, though ambiguous, terms of his anthropology and spirituality. As a synonym for the inner man (homo interior) it encompasses the whole affective, intellectual, moral and religious life. In this sense, it is the privileged place for a personal encounter with God. The analysis of Augustine’s writings reveals a link between the concept of the Trinity and indications concerning the spiritual life of man. Reflections on the “heart” can be put into a kind of triptych: creation “in the image of God,” illumination by Christ, and dilatation by the Holy Spirit. The impact of God on the human heart should find its completion in a voluntarily adopted attitude of adoration, humility and love.